Clinical Analysis and Prognostic Prediction Model for Patients with Uterine Leiomyosarcoma at FIGO Stage I - Chen S; Deng Y; Zhai Y; Zhan Y; Li X; Wang J; Bai H (Dove Medical Press, 2023)
Shuya Chen,1 Yunhan Deng,2 Yan Zhai,2 Yang Zhan,3 Xue Li,4 Jiandong Wang,1 Huimin Bai2 1Department of Gynecological Oncology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Beijing, People's Republic of China; 2Department of Obstetrics and Gynecology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People's Republic of China; 3Department of Pathology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Beijing, People's Republic of China; 4Department of Pathology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Jiandong Wang, Department of Gynecological Oncology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Qihelou Street, Dongcheng District, Beijing, 100006, People's Republic of China, Tel +0086-13910566755, Email wangjiandongxy@ccmu.edu.cn Huimin Bai, Department of Obstetrics and Gynecology, Beijing Chao-Yang Hospital, Capital Medical University, No. 8, North Road of Workers Stadium, Chaoyang District, Beijing, 100020, People's Republic of China, Tel +0086-01085231765, Email bhmdoctor@sina.comPurpose: To reveal the clinical status and construct a predictive prognostic model for patients with uterine leiomyosarcoma (uLMS) at International Federation of Gynecology and Obstetrics (FIGO) stage I.Patients and Methods: The medical records of patients with stage I uLMS during the study period were retrospectively reviewed. Multiple imputation, Martingale residuals and restricted cubic spline were used for data processing. Univariate and multivariate analyses were used to determine independent prognostic factors. The Schoenfeld individual test was used to verify the proportional hazards (PH) assumption. The predictive ability of the nomogram was validated internally.Results: Ultimately, 102 patients were included. The median age at diagnosis was 51 years old. During the medium follow-up time of 68 months, 55 (53.9%) patients developed recurrence. The median recurrence interval was 32 months. The most common metastatic site was the lung (27 cases). Eventually, 38 (37.3%) patients died of uLMS. The 3-year and 5-year overall survival rates were 66.0% and 52.0%, respectively. Age at diagnosis > 49 years, larger tumor size, MI> 10/10HPF, presence of LVSI and Ki-67 labeling index (LI) > 25% (P=0.0467, 0.0077, 0.0475, 0.0294, and 0.0427, respectively) were independent prognostic factors. The PH assumption remained inviolate. The concordance index was 0.847, the area under the time-dependent receiver operating characteristic curve surpassed 0.7, and the calibration curve showed gratifying consistency.Conclusion: Age at diagnosis, tumor size, MI, LVSI, and Ki-67 LI were identified as independent prognostic factors for stage I uLMS. This prognostic nomogram would provide personalized assessment with superior predictive performance.Keywords: uterine leiomyosarcoma, prognosis, nomogram, risk stratification